Acceptance sampling plans based on truncated life tests for extended exponential distribution - Amer Al-Omari; Said Al-Hadhrami (Kuwait Journal of Science)
In this paper, acceptance sampling plans are suggested for the extended exponential distribution mean, when the life time test is truncated at a pre-fixed time. The minimum sample sizes needed to assert the specified life mean are presented under a given customer,s risk. The operating characteristic function values of the proposed sampling plans and producer,s risk are provided. Some tables are given and the results are illustrated by numerical examples. An application of a real data set reveals that the proposed acceptance sampling plans can be used in the industry.